Technological Obsolescence - Ma, Song (Review of Financial Studies, 2025)
This paper proposes a new measure of technological obsolescence using detailed patent data. The measure contains incremental information about firm innovation relative to measures focusing on new innovation. Using this measure, we present two sets of results. First, firms’ technological obsolescence foreshadows substantially lower growth, productivity, and reallocation of capital. This finding mainly applies to obsolescence of core innovation and embodied innovation, and it is stronger in competitive product markets. Second, in stock markets, high-obsolescence firms underperform low-obsolescence firms by 7% annually. Using analyst forecast data, we show this is due to a systematic overestimation of future profits of obsolescent firms.